Overview of research progress on blind separation methods for single channel communication signal - Wen DENG; Zhitao HUANG; Xiang WANG (Tongxin xuebao)
Significant progress has been made in the research of single channel blind signal separation (SCBSS) methods, as the theoretical and practical applications of SCBSS technology have been continuously improved.A new classification framework for blind signal separation (BSS) of communication signal problems was proposed based on an analysis of a large number of academic research results from both domestic and international sources.The division of SCBSS problems into four levels: multi-signal waveform separation, single-signal waveform separation, multi-signal symbol sequence separation, and single-signal symbol sequence separation was determined by taking into consideration the demand for output results of BSS systems in different application scenarios.Subsequently, the research status of SCBSS methods was systematically reviewed.Furthermore, the current research status of data-driven SCBSS was summarized, and the problems and solutions that needed to be addressed in data-driven SCBSS technology were explored.Finally, several potential research directions for SCBSS were analyzed and forecasted.The aim is to provide a reference for the research and application of SCBSS.